Empreendedorismo imigrante da comunidade brasileira na região do Porto em Portugal - Silva, Henrique Souza da (2021)
This dissertation comprises a study that aims to describe the patterns of entrepreneurship in the Brazilian community in the Porto Region in Portugal, in order to outline a structure, of a possible model that explains the phenomenon of Brazilian immigrant entrepreneurship, in the light of the Brazilian migratory flow, regarding to their aspirations, migratory trajectories and aspects of their entrepreneurial activities. To accomplish this main objective, a data survey that will include several sources is necessary, aiming at robustness and triangulation of research data. As sources of quantitative data, a survey of data from official sources in Portugal, as well as from the Brazilian Ministry of Foreign Affairs, will be used. In addition, it was possible to characterize the sociodemographic profile of Brazilian immigrants in Portugal and the interviewees who are members of the Brazilian entrepreneurial community. Regarding the qualitative data collection, a qualitative exploratory research was conducted through the analysis of 35 in-depth interviews with Brazilian entrepreneurs from various sectors, established in the region of Porto. Participant observation and field notes complemented the strategy. The main results show the reasons that lead immigrants to leave Brazil and settle in Portugal, the main characteristics of entrepreneurs in the Porto region, how their business opportunities and barriers are configured, including marketing choices and networking mechanisms. Thus, the study highlights the profile of Brazilian entrepreneurs in Portugal, their behavioral traits, describing their businesses and the relationships among entrepreneurs and between entrepreneurs and their community. By observing the scenario of Brazilian entrepreneurship in Portugal, the study contributes to the understanding of the constitution and structuring of the businesses of Brazilian immigrants, the related and conditioning factors. Its contribution to management stems from the possibility of supporting Brazilian immigrant entrepreneurs to glimpse paths, based on the cases reported, so that they act with greater assertiveness in the management of their businesses.